Economic policy in a highly dollarized economy : the case of Cambodia - Zamaróczy, Mario de (IMF WashingtonUS, 2003)
Presents a short description of economic, financial and structural developments in Cambodia since independence, focusing on the decade ending in 2001. Reviews recent developments in the literature on dollarization and discusses the degree of dollarization in Cambodia. Examines costs and benefits of dollarization in Cambodia and discusses the ensuing macroeconomic policy implications.